2017
DOI: 10.1016/j.drugalcdep.2017.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco toxicant exposure in cigarette smokers who use or do not use other tobacco products

Abstract: Background Non-cigarette other tobacco products (OTP; e.g., cigarillos, little cigars) are typically used in combination with cigarettes, but limited data exists on the tobacco toxicant exposure profiles of dual cigarette-OTP (Cig-OTP) users. This study examined biomarkers of nicotine and carcinogen exposure in cigarette smokers who used or did not use OTP. Methods 111 Cig-OTP and 111 cigarette only (Cig Only) users who smoked equivalent cigarettes per day were matched on age (< 40, >= 40), race (African Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Tobacco toxicant exposure varies depending on type and number of products used (Goniewicz et al, 2017, Nollen et al, 2017. For example, in some studies, exclusive use of electronic nicotine delivery systems (electronic cigarettes, ECIGs) was associated with lower levels of exposure to toxicants including TSNAs, VOCs, and PAHs, relative to exclusive combustible cigarette smoking (Shahab et al, 2017, Goniewicz et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco toxicant exposure varies depending on type and number of products used (Goniewicz et al, 2017, Nollen et al, 2017. For example, in some studies, exclusive use of electronic nicotine delivery systems (electronic cigarettes, ECIGs) was associated with lower levels of exposure to toxicants including TSNAs, VOCs, and PAHs, relative to exclusive combustible cigarette smoking (Shahab et al, 2017, Goniewicz et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies evaluating the impact of tobacco product use on biomarkers of exposure used conventional techniques (Nollen et al, 2017, such as pairwise t-tests and analysis of variance, to examine group differences in geometric means of individual tobacco biomarkers. These conventional techniques are useful in describing how a particular biomarker may vary across groups.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Another study reported that cigarette plus other tobacco product users had lower nicotine and carcinogen levels relative to exclusive cigarette smokers. 12 These conflicting results suggest that additional research is needed to better understand how the frequency of use and type of products that are being dual and poly used may impact associations with levels of biomarkers of nicotine and exposure to carcinogens.…”
mentioning
confidence: 99%
“…Smoking topography determines the exposure to toxicants, which has disease implications. Individuals who use non-cigarette tobacco products (including individuals who use LCC) had lower urinary nicotine, cotinine, total nicotine equivalents, and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) levels compared to individuals who smoke only cigarettes, despite reporting similar past 7-day tobacco product use [ 50 ]. The differences in smoking topography between the products could account for the differences in exposure, but smoking topography was not evaluated in this study.…”
Section: Resultsmentioning
confidence: 99%